Global merger control—where to now?. (9th September 2019) - Levy, Nicholas; Waksman, Alexander; Sheridan, Lanto
Abstract: Considerable progress has been made over the past 30 years in ensuring that US and EU merger control norms are broadly understood and respected; that decisions are taken by independent agencies unfettered by political influence; and that agencies cooperate with each other to avoid divergent outcomes. Notwithstanding these achievements, important challenges remain. In particular, the broad consensus around the objectives and architecture of merger control is increasingly being questioned. This article identifies the principal strengths of global merger control, describes its major challenges, and considers ways to modernize and strengthen the existing system.